A randomized clinical trial comparing early patient-reported pain after open anterior mesh repair versus totally extraperitoneal repair of inguinal hernia. Issue 12 (13th November 2021) - Matikainen, Markku; Vironen, Jaana Hellevi; Silvasti, Seppo; Ilves, Imre; Kössi, Jyrki; Kivivuori, Antti; Paajanen, Hannu
Abstract: Background: This was a prospective, multicentre, non-blinded, randomized clinical trial involving two parallel groups of patients. Methods: Adult patients with symptomatic unilateral primary inguinal hernia were included in this study. Patients were enrolled and treated in five Finnish hospitals. Eligible patients were randomized by use of a computer-based program to receiving either open anterior repair (modified Lichtenstein) with glue mesh fixation or totally extraperitoneal (TEP) repair. The primary aims were to compare 30-day patient-reported pain scores and return to work after surgery between the two groups. Results: A total of 202 patients were randomized: 98 patients to TEP repair and 104 patients to open repair. All randomized patients received their allocated treatment. A total of 86 patients (88 per cent) in the TEP group and 94 patients (90 per cent) in the Lichtenstein group completed the 30-day follow-up. Patients experienced less early pain ( P  < 0.001) and used less analgesics after TEP repair, compared to those who had modified Lichtenstein repair. Two patients in the TEP group and five in the Lichtenstein group developed superficial wound infection ( P  = 0⋅446). Only one reoperation was performed in the Lichtenstein group due to haematoma. Conclusion: TEP inguinal hernia repair is associated with less early postoperative pain compared to the open glue mesh fixation technique. Trial registration: NCT03566433 (http://www.clinicaltrials.gov ). Lay Summary: In this randomized clinical trial, we compared two different operating techniques for inguinal hernia repair. Patients were randomized to receiving either open or laparoscopic inguinal hernia repair. After the operation, patient-reported pain and functional outcomes were compared. Patients experienced less pain after laparoscopic repair. Abstract : In this randomized clinical trial, we compared totally extraperitoneal (TEP) repair of groin hernia to open repair of groin hernia. The main outcome was patient-reported pain scores within the first 30 days after the index operation. Patients experienced less pain after TEP repair, compared to those who had open repair.